Socio-demographic factors associated with dietary behaviour among young Ghanaians aged 15-34 years (2016)
This study used data from the 2008 Ghana Demographic and Health Survey to investigate the association between selected sociodemographic factors and dietary behaviour as measured by fruit and vegetable consumption among a sample of 6139 young people aged 15–34 years in Ghana. Overall, fruit and vegetable consumption was low in young people, but females were likely to consume more fruit and vegetables than their male counterparts. Respondents from the Mande ethnic group, those who resided in rural areas and those living in the Brong/Ahafo, Ashanti and the Eastern regions consumed more fruit and vegetables than those from other regions. Females who were Catholic/Anglican, Methodist/Presbyterian and Pentecostal/Charismatic were more likely than those of other religions to consume fruit and vegetables, while Muslim males generally consumed more fruit and vegetables. The findings point to the need for interventions to educate young people in Ghana about the health benefits of eating fruit and vegetables.